2022
DOI: 10.3389/fphar.2022.934534
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids as Modulators of EMT in Invasive Cancers: A Review of Molecular Targets With the Contribution of Malignant Mesothelioma Studies

Abstract: Curcuminoids, which include natural acyclic diarylheptanoids and the synthetic analogs of curcumin, have considerable potential for fighting against all the characteristics of invasive cancers. The epithelial-to-mesenchymal transition (EMT) is a fundamental process for embryonic morphogenesis, however, the last decade has confirmed it orchestrates many features of cancer invasiveness, such as tumor cell stemness, metabolic rewiring, and drug resistance. A wealth of studies has revealed EMT in cancer is in fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 340 publications
(300 reference statements)
0
10
0
Order By: Relevance
“…The parallel decrease in PAK1 also attests to the reduced progression stage of the curcumin-treated tumors, as this effector of the Rho GTPases (encoded by Pak1 ), involved in cell motility and cytoskeleton remodeling, is overexpressed in almost all tumors [ 60 ]. Finally, one last line of evidence of this reduced invasiveness is given by the decrease in the Ena/VASP-like protein (encoded by Evl ), which organizes stress fibers leading to cancer cell stiffening [ 52 ], with stiffness playing an important role in the harmful effects of epithelial-to-mesenchymal transition (EMT) in invasive cancers [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parallel decrease in PAK1 also attests to the reduced progression stage of the curcumin-treated tumors, as this effector of the Rho GTPases (encoded by Pak1 ), involved in cell motility and cytoskeleton remodeling, is overexpressed in almost all tumors [ 60 ]. Finally, one last line of evidence of this reduced invasiveness is given by the decrease in the Ena/VASP-like protein (encoded by Evl ), which organizes stress fibers leading to cancer cell stiffening [ 52 ], with stiffness playing an important role in the harmful effects of epithelial-to-mesenchymal transition (EMT) in invasive cancers [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…IRF2BPL is one of three members of a family of transcriptional regulators that potentially control various hallmarks of oncogenesis, including tumor suppression depending on the context [ 79 ]. A recent work has demonstrated that it downregulates Wnt signaling by interacting with and targeting β-catenin (crucial markers of EMT in cancer [ 67 ]) for proteasomal degradation [ 80 ]. The second protein, a member of the hexokinase family encoded by Hk3 , participates in tumor immune microenvironment remodeling and promotes immune escape, with its high expression leading to a poor prognosis in patients with renal carcinoma [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids have a variety of positive health effects, such as anti-bacterial, anti-cancer, anti-osteoporosis, and anti-viral functions [44]. In this type of compound, quercetin (4), silybin ( 5), baicalein (6), genistein (10), hesperidin (11), and naringenin (12) have been reported to have EMT inhibitory effects (Figure 4).…”
Section: Flavonoidsmentioning
confidence: 99%
“…During this process, cells undergo morphological changes associated with the repression of epithelial markers and the acquirement of mesenchymal marker proteins. The most notable marker of epithelial cells is E-cadherin, while N-cadherin is the most representative marker of mesenchymal-type cells [ 12 ]. The switch from E-cadherin to N-cadherin is often used for the identification of EMT processes.…”
Section: The Regulation Of the Emt Process And Its Roles In Cancer Pr...mentioning
confidence: 99%
See 1 more Smart Citation